2019
DOI: 10.3390/su11195495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Travel Mode Choice Behavior Considering the Indifference Threshold

Abstract: An effective way to optimize traffic structures is by changing travel costs, thereby moving travelers from private transportation to public transportation. However, according to the existing studies, the traveler will not transfer from one mode to another unless the change in travel utility is greater than the indifference threshold. Therefore, the “indifference threshold” is one of the most important factors influencing a traveler’s choice of behavior. This study defines the “indifference threshold” as the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Numerous studies have indicated that travelers tend to choose cheaper modes of transport [43,44]. In addition, studies have shown that these variables have the highest impact on a traveler's mode choice behavior [45][46][47][48]. Among socioeconomic variables, the variables that significantly contributed to the mode choice are monthly income, gender, education level and age.…”
Section: The Modelmentioning
confidence: 99%
“…Numerous studies have indicated that travelers tend to choose cheaper modes of transport [43,44]. In addition, studies have shown that these variables have the highest impact on a traveler's mode choice behavior [45][46][47][48]. Among socioeconomic variables, the variables that significantly contributed to the mode choice are monthly income, gender, education level and age.…”
Section: The Modelmentioning
confidence: 99%
“…Thus, these theories are particularly relevant to the present study. Within the field of sustainability, they covered a large variety of contexts and behaviors: restauration [70], driving [71], transport and travel mode choice [72][73][74][75], green products and food [76][77][78], waste management, recycling [79,80], and agriculture [81,82].…”
Section: Theory Of Reasoned Action (Tra) and Theory Of Planned Behavimentioning
confidence: 99%
“…However, the potential shift away from passenger car use has to account for constrained daily travel time budget and activity space [5,6]. Specifically, understanding potential for modal shift requires comparing travel times of alternative modes for individual travelers, as they can influence travelers' decisions [7]. From the standpoint of steering sustainability transitions, understanding the potential for modal shift by taking into account changes in travel time, carbon emissions, and physical activity is important for large infrastructural investments, such as public transport network overhauls [8], or for piloting new mobility services and policy programs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%